DETECTION OF VIRULENCE GENES IN ENVIRONMENTAL STRAINS OF Vibrio cholerae FROM ESTUARIES IN NORTHEASTERN BRAZIL - Menezes, Francisca Gleire Rodrigues de; Neves, Soraya da Silva; Sousa, Oscarina Viana de; Vila-Nova, Candida Machado Vieira Maia; Maggioni, Rodrigo; Theophilo, Grace Nazareth Diogo; Hofer, Ernesto; Vieira, Regine Helena Silva dos Fernandes (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The objectives of this study were to detect the presence of Vibrio cholerae in tropical estuaries (Northeastern Brazil) and to search for virulence factors in the environmental isolates. Water and sediment samples were inoculated onto a vibrio-selective medium (TCBS), and colonies with morphological resemblance to V. cholerae were isolated. The cultures were identified phenotypically using a dichotomous key based on biochemical characteristics. The total DNA extracted was amplified by PCR to detect ompW and by multiplex PCR to detect the virulence genes ctx, tcp, zot and rfbO1. The results of the phenotypic and genotypic identification were compared. Nine strains of V. cholerae were identified phenotypically, five of which were confirmed by detection of the species-specific gene ompW. The dichotomous key was efficient at differentiating environmental strains of V. cholerae. Strains of V. cholerae were found in all four estuaries, but none possessed virulence genes.